A review of the intrinsic ductility and toughness of hard transition-metal nitride alloy thin films - Kindlund, H.; Sangiovanni, D.G.; Petrov, I.; Greene, J.E.; Hultman, L. (Thin solid films, 2019)
Over the past decades, enormous effort has been dedicated to enhancing the hardness of refractory ceramic materials. Typically, however, an increase in hardness is accompanied by an increase in brittleness, which can result in intergranular decohesion when materials are exposed to high stresses. In order to avoid brittle failure, in addition to providing high strength, films should also be ductile, i.e., tough. However, fundamental progress in obtaining hard-yet-ductile ceramics has been slow since most toughening approaches are based on empirical trial-and-error methods focusing on increasing the strength and ductility extrinsically, with a limited focus on understanding thin-film toughness as an inherent physical property of the material. Thus, electronic structure investigations focusing on the origins of ductility vs. brittleness are essential in understanding the physics behind obtaining both high strength and high plastic strain in ceramics films. Here, we review recent progress in experimental validation of density functional theory predictions on toughness enhancement in hard ceramic films, by increasing the valence electron concentration, using examples from the V1-xWxN and V1-xMoxN alloy systems.